Preparation of photocatalyst membrane from natural rubber with titanium dioxide and zeolite - Nghiêm, Thị Thương; Nguyễn, Thị Hương; Trần, Thị Thúy; Nguyễn, Phạm Duy Linh (JST: Engineering And Technology For Sustainable Development, 2021)
A simple method for the preparation of a catalyst membrane from natural rubber with titanium dioxide and zeolite A was presented in this work. This simple method was based on the mixing TiO2 suspension (anatase phase), zeolite suspension in NH4OH with natural rubber latex and subsequently casting the mixture into membrane followed by drying at 50°C. The characteristics of the composite membrane was studied by using scanning electron microscopy (SEM), X-ray diffractometer (XRD) techniques and mechanical properties measurements. The photocatalytic activity of the HANR/TiO2/ZA was evaluated using methylene blue (MB) as a model for organic dye pollutant in water. The results showed that the catalyst membrane prepared with a small amount of TiO2 together with Zeolite A could rapidly degrade MB dye solution in water under UV light irradiation. The effect of amount of Zeolite A on the degradation of MB was also investigated. Furthermore, we evaluated the reusability of the membrane and the result showed that the catalytic ability of the membrane on MB degradation decreased a little. The mechanical property of the catalyst membrane was slightly decreased after recycling.